When does marketing & sales collaboration affect the perceived lead quality? The moderating effects of IT systems - Lukas Hilke (Junior Management Science (JUMS), 2024)
In the realm of corporate dynamics, lead management remains a relatively underexplored subject, despite its increasing significance and annual resource allocation. This study addresses the enigmatic "sales lead black hole" by investigating the influence of enhanced collaboration between marketing and sales on the perceived quality of marketing-generated leads. A research model was crafted to delve into this relationship and assess the impact of contemporary IT systems on collaboration, subsequently bolstering the perceived lead quality. Findings reveal that active collaboration in planning lead management activities and exchanging information elevates the acceptance of marketing-generated leads, prompting increased follow-up engagement by sales personnel. IT systems play a pivotal role in fostering such collaboration, amplifying its effect on the perceived quality of leads. This research contributes vital insights for scholars by dissecting key drivers of perceived lead quality and proposing solutions for the sales lead black hole. For practitioners, the study offers actionable implications to enhance subjective perceptions of marketing-generated leads, curbing resource wastage through improved follow-up strategies.
Keywords: 650; IT-systems; lead management; marketing & sales collaboration; perceived lead quality; sales engagement